Análisis a los estados financieros de la cooperativa de ahorro y crédito Guamote ltda., en el cantón Guamote, provincia de Chimborazo, periodo 2013 –2014 - Quingue Manguia, Rosa María (2017)
This thesis work was carried out to put into practice the knowledge acquired in a real and relevant way, training the accounting professional in one of its fields of action, in addition the requirement for graduation is fulfilled, prior to obtaining the grade of Engineer in Accounting and Auditing CPA. By carrying out the present work, it is possible to comply with the specific objectives set out in the thesis project and which refer to using techniques and tools to execute the Vertical Analysis that determines the Cooperative's organizational structure and with the Horizontal the variations are established of the accounts from one period to another, in the cycles subject to study, as well as applying the PERLAS monitoring system, to identify their real Economic and Financial Situation and contribute to the successful decisions in the Cooperativist field. Once the research work is completed among the main conclusions, it can be stated that the cooperative requires financial analysis as a mechanism to study the behavior of its financial statements at a given time and, above all, to issue recommendations based on real data and attached to the reality of the Cooperative. The result obtained in the investigation reveals situations of different nature that are presented in the analyzed accounts, so it is necessary to implement corrective measures with recommendations to optimize the use of economic resources and avoid possible scenarios that affect the financial entity, through the implementation of adequate internal controls.